Effects of Ultrasonic Treatment Combined with Microporous Modified Atmosphere Packaging on Cold Storage Quality of Fresh-cut Jackfruit - Aiping FAN; Qiuhong DENG; Liping ZENG; Guangming YANG; Yubing LI; Chunyan LIU (Shipin gongye ke-ji, 2025)
The aim of this study was to investigate the effects of ultrasonic (US) treatment combined with microporous modified atmosphere packaging (MMAP) on the microbial count and refrigerated quality of fresh-cut jackfruit, and to determine the optimal means of preservation. This study employed four treatment methods for fresh-cut jackfruit: control (distilled water, 10 min), US (300 W, 10 min), MMAP (distilled water, 10 min, 5% O2, 6% CO2, 15 holes), and US+MMAP. Samples were stored at 10±1 ℃ for 8 d and microbial and physicochemical parameters were measured every 2 d. The results showed that compared with the control treatment, all three treatments significantly inhibited the growth and reproduction of bacteria, mold, and yeast in fresh-cut jackfruit during refrigerated storage (P<0.05), effectively delaying spoilage caused by these microorganisms. Additionally, these treatments maintained higher tissue firmness, total soluble solid content, titratable acidity, vitamin C content, and total phenolic content in fresh-cut jackfruit, while reducing the malondialdehyde content and polyphenol oxidase and peroxidase activity, thereby inhibiting browning. Notably, the US+MMAP combined treatment was significantly superior to the individual treatments. In summary, ultrasonic and microporous modified atmosphere packaging treatment has a good preservative effect on fresh-cut jackfruit.